Comparative analysis of the polymerase chainreaction and the hybridcapture assay for the detection of human papilomavírus infection - Carvalho, Maria Odete O.; Carestiato, Fernanda N.; Ribeiro, Marisa O.; Marinho, Marcia; Barbosa, Fabio M.; Silva, Licínio E.; Dimetz, Trude; Oliveira, Ledy H.S.; Cavalcanti, Silvia M.B. (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction: cervical cancer is the second major cause of death from cancer in female worldwide. From 2000, World Health Organization acceptedthe Human Papillomavirus (HPV) as the etiological agents of cervical cancer. Nevertheless, the diagnosis of such viral infections still needs improve-ments. Objective:to evaluate the use of molecular methodologies to access HPV DNA, in association to Cytopathology, the classical method ofscreening cervical lesions. Method: the research was conducted by using samples from cervical smears of women attended at Laboratórios Dr SérgioFranco, at Rio de Janeiro, among 2000. They were analyzed by the hybrid capture assay II (HCA II) and the polymerase chain reaction (PCR) withgeneric primers MY 09/MY 11. The study was composed by 40 patients aging from 17 to 41 years old. The comparative analysis between HCA II andPCR was conducted with the objective to determine the sensibility and the specificity of HCA II. Results: HPV was detected in 75% of the samples, byHCA II, while PCR showed HPV in 70% of the patients. Cytopathology was used as a reference method of screening the lesions. The three testsshowed absolute agreement when cytopathology referred the sample as NORMAL, HPV and High grade lesion (HSIL). Disagreements occurred whencytopathology pointed low squamous intraepithelial lesions (LSIL), in which HCA II showed 100% of HPV detection and PCR pointed only 85% ofDNA detection. After comparing the two molecular techniques with cytopathology results, we observed that in HCA II (p = 0) as well as in PCR (p =0.002) a positive association was demonstrated. Conclusion: hence, we concluded that, despite a few disagreements, HCA II showed to be sensitiveand specific enough to be used in combination with cytopathology. Besides that, the evaluation of viral load measures obtained by HCA II showed tobe related to the severity of the lesion and merits further studies to analyze possible association to risk of progression to malignancy.